1999
DOI: 10.1161/01.str.30.5.1043
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Brain Ischemic Change on MRI

Abstract: Background and Purpose-Specific change of persistent hyperintensity/hypointensity on T1-weighted (T1W) and T2-weighted (T2W) MRI, respectively, has been reported to develop in the human basal ganglia after brief hemispheric ischemia. We investigated whether this ischemic change observed in humans could be reproduced experimentally in rats after brief middle cerebral artery (MCA) occlusion (MCAO), and if so, what the neuroradiological change represented histologically. Methods-The origin of the right MCA of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Similarly intriguing following temporary MCA occlusion in the rat is the observation of delayed hyperintensity on T1-weighted with hypointensity on T2-weighted MRI affecting the striatum, with histopathological evidence of SNL and reactive microglia [32, 33]. Interestingly, similar MRI findings have been observed in stroke patients with spectacular shrinking deficit, involving both the basal ganglia and cortex, despite normal CT scans and complete clinical recovery [34].…”
Section: Selective Neuronal Lossmentioning
confidence: 87%
“…Similarly intriguing following temporary MCA occlusion in the rat is the observation of delayed hyperintensity on T1-weighted with hypointensity on T2-weighted MRI affecting the striatum, with histopathological evidence of SNL and reactive microglia [32, 33]. Interestingly, similar MRI findings have been observed in stroke patients with spectacular shrinking deficit, involving both the basal ganglia and cortex, despite normal CT scans and complete clinical recovery [34].…”
Section: Selective Neuronal Lossmentioning
confidence: 87%
“…It has been reported that calcium deposits reduce both T1 and T2 relaxation times, leading to hyper-intensities on T1-WI and hypo-intensities on T2-WI (Dell et al 1988). Selective neuronal necrosis and gliosis have the same MRI pattern (Fujioka et al 1999). In three of five animals with mineralization spots, hyper-intensities on T1-WI have been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors suggest microhaemorrhage as a cause [7], while other studies failed to demonstrate microhaemorrhage histopathologically, suggesting calcium deposition as the favoured aetiology [3]. Others consider cerebral ischemia as the most appropriate explanation of the T1 signal alteration [8, 9]. …”
Section: Discussionmentioning
confidence: 99%